2020
DOI: 10.1186/s12882-020-02120-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between health-related hope and adherence to prescribed treatment in CKD patients: multicenter cross-sectional study

Abstract: Background In chronic kidney disease (CKD), patients’ adherence to prescriptions for diet and for medications might depend on the degree to which they have hope that they will enjoy life, and that hope could vary with the stage of CKD. The aims of this study were to quantify both the association of CKD stage with health-related hope (HR-Hope), and the association of that hope with psychological and physiological manifestations of adherence. Methods This was a cross-sectional study involving 461 adult CKD pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 28 publications
(40 reference statements)
3
13
1
Order By: Relevance
“…Kurita et al used a health-related hope score in pre-and post-dialysis CKD patients and found that patients with higher hope to enjoy life were associated with lower perception of burden of fluid and diet restriction and better systolic blood pressure. 39 Furthermore, the correlations of SWB scores with HRQOL in our study were rather weak which supported the idea that SWB aspects of spirituality are distinct and separate constructs. In other words, it does not seem that spirituality has considerable overlap with other PRO parameters, suggesting that SWB is a unique dimension of HRQOL.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Kurita et al used a health-related hope score in pre-and post-dialysis CKD patients and found that patients with higher hope to enjoy life were associated with lower perception of burden of fluid and diet restriction and better systolic blood pressure. 39 Furthermore, the correlations of SWB scores with HRQOL in our study were rather weak which supported the idea that SWB aspects of spirituality are distinct and separate constructs. In other words, it does not seem that spirituality has considerable overlap with other PRO parameters, suggesting that SWB is a unique dimension of HRQOL.…”
Section: Discussionsupporting
confidence: 72%
“…Nevertheless, there was a previous study from Japan supporting the idea that SWB may associate with improved HRQOL. Kurita et al used a health‐related hope score in pre‐ and post‐dialysis CKD patients and found that patients with higher hope to enjoy life were associated with lower perception of burden of fluid and diet restriction and better systolic blood pressure 39 . Furthermore, the correlations of SWB scores with HRQOL in our study were rather weak which supported the idea that SWB aspects of spirituality are distinct and separate constructs.…”
Section: Discussionsupporting
confidence: 62%
“…Moreover, further research is needed to ascertain if SOC is conceptually different from self-efficacy, hope, and resilience. This is an important question to address specifically in this patient-population, especially that, for example, studies have shown that hope is associated with a decreased burden of fluid and dietary restriction in dialysis patients [ 75 ] and is associated with a decreased incidence of the decline in physical function [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a preventive role of hope for mental status, such as depression and anxiety, has been noted in patients with SLE. [18] Considering that high levels of hope may contribute to lower burden on self-management and better blood pressure control among patients with chronic kidney disease, [15] health-related hope may serve as a psychological factor that drives continuing successful self-management, regardless of the type of chronic disease.…”
Section: Discussionmentioning
confidence: 99%